Potential of Butterfly Pea Flower (Clitoria Ternatea) Extract as an Antidiabetic Agent - Ariyanto, Muhammad Wahyu; Lestari, Puput Legia; Wafda Safanah Nadhiroh; Sulastri, Afianti; Amalia, Linda; Somantri, Budi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to insulin deficiency or insulin resistance. Currently available pharmacological treatments often cause unwanted side effects, so alternative therapies that are safer and more effective are needed. This study aims to analyze the effectiveness of telang flower extract in reducing blood glucose levels and preventing complications. The potential of Clitoria ternatea as an antidiabetic agent was explored through a systematic literature review, using scientific databases such as Google Scholar, ScienceDirect, and Mendeley with the keywords “Clitoria ternatea AND diabetes AND blood glucose.” Inclusion criteria applied included experimental studies conducted on diabetes-induced mice samples, interventions with telang flower extract administration, and publications within the last 5 years (2021-2025). From a total of 1,858 articles identified, by applying the PRISMA-ScR method, 8 articles were obtained that met the inclusion criteria. The analysis showed that telang flower extract was effective in reducing blood glucose levels. This antidiabetic effect is thought to be due to the presence of flavonoids and other bioactive compounds in telang flowers that act as α-amylase enzyme inhibitors, antioxidants, and anti-inflammatories. These findings indicate the potential of Clitoria ternatea as a promising therapeutic alternative in the management of diabetes mellitus.